Parkinson’s disease is associated with altered expression of CaV1 channels and calcium-binding proteins - Hurley, Michael J.; Brandon, Bianca; Gentleman, Steve M.; Dexter, David T. (Brain (London, England : 1878), 2013)
In Parkinson's disease oxidative stress and calcium-induced excitotoxicity have been considered important mechanisms leading to cell death for decades, but the factors that make some neurons vulnerable to neurodegeneration while others remain resistant are not fully understood. Studies of the disorder in animal models suggest that the voltage-gated calcium channel subtype Ca(V)1.3 has a role in making neurons susceptible to neurodegeneration and support earlier work in post-mortem human brain that suggested loss of calcium buffering capacity in neurons correlated with areas of neuronal loss in the substantia nigra of parkinsonian brain. This study examined expression of Ca(V)1 subtypes and the calcium-binding proteins calbindin, calmodulin and calreticulin in areas vulnerable and resistant to neurodegeneration in Parkinson's disease, in brain from neurologically normal individuals and patients with Parkinson's disease. In control brain the expression of a specific Ca(V)1 subtype or distribution of each calcium-binding protein did not associate with those regions prone to neurodegeneration in Parkinson's disease. Whereas, alterations in the amount of both Ca(V)1 subtypes and the calcium-binding proteins were found throughout the brain in Parkinson's disease. Some changes reflected the cell loss seen in Parkinson's disease, whereas others represented altered levels of cellular expression, which as they occurred in the absence of cell loss could not be explained as solely compensatory to the neurodegeneration. The finding of increased Ca(V)1.3 subtype expression in the cerebral cortex of early stage Parkinson's disease, before the appearance of pathological changes, supports the view that disturbed calcium homeostasis is an early feature of Parkinson's disease and not just a compensatory consequence to the neurodegenerative process. This interpretation is supported further by the finding that the ratio of Ca(V)1 subtypes differed throughout the brain in patients with Parkinson's disease compared with control subjects, in favour of an increased use of Ca(V)1.3, which would add to the metabolic burden for cells that rely on this Ca(V)1 subtype for electrical activity and could therefore render specific neuronal populations more vulnerable to neurodegeneration.